Is Hydrogen Peroxide Disinfection Effective for Cleaning Pollen Particles Attached to Contact Lenses? - Sunaga, Takahiro (Clin Optom (Auckl), 2020)
PURPOSE: It has been proven that wearing soft contact lenses (SCLs) can make pollen-induced allergic conjunctivitis worse. We investigated the cleaning effect of disinfectants and rinsing solution on cedar pollen attached to SCLs. METHODS: Two-week replacement disposable SCLs, to which pollen particles were experimentally attached, were washed and cleaned with either saline of rinsing solution (n = 10) or 3% hydrogen peroxide (n = 10). We observed, under a microscope, the cedar pollen adhered to the SCLs after washing. RESULTS: The number of residual pollens attached to SCLs was 23.7 ± 25.7 with rinsing solution and 0.2 ± 0.6 with 3% hydrogen peroxide solution per single area (100 µm × 100 µm). The percentage of adhesion area of pollen to the SCLs was 0.9 ± 1.1% with rinsing solution and 0.0 ± 0.0% with 3% hydrogen peroxide solution. There were significant differences in the number of pollen and adhesion areas of pollen between the two groups (p < 0.05 and p < 0.05, respectively). CONCLUSION: These results suggest that hydrogen peroxide solution is superior in cleaning effect of cedar pollen attached to SCLs compared to saline.